Strategi Pengembangan BUMDesa yang Berdaya Saing di Era Digitalisasi Melalui Pemanfaatan Teknologi Informasi - Nurkhalik Wahdanial Asbara; Nurrachma Nurrachma; Muhammad Hidayat; Nurhaeda Z; Nurul Izzanurdin; Adella Viana; Rifai Al Ailmunur (Politeknik Negeri Cilacap, 2023)
BUMDesa must improve rural welfare in line with the digital era. Data collection, administration, and outreach are still carried out manually in many villages, as well as the lack of cooperation between related parties which causes the welfare of the villagers to not be optimal. The method used is lecture, simulation and question and answer. The result of this activity is that people's awareness and understanding of technological developments increases and with the completion of the activity it is hoped that the community can utilize technology in carrying out their daily activities in managing their business.